EXPLORING VEGETABLE FARMING IN PERI-URBAN AREAS OF JAKARTA (A CASE STUDY OF TANGERANG REGENCY) (Jurnal Social Economic of Agriculture, 2019)
The presence of vegetable farmers in peri-urban areas is essential for the supply of food to the urban population. However, they face intense competition from other non-agricultural activities. This research aims to explore the characteristics of vegetable farmers in Tangerang Regency as part of Jakarta Metropolitan Area, the motivation of respondents towards becoming vegetable farmers, and their strategy in adapting to massive urban development. We employed the qualitative approach by combining questionnaires, field observations, and interviews. We found the new entrant farmers that are in their productive ages and came with experience in the formal economy before starting farming. The motivation of respondents became vegetable farmers vary depend on their background and the land ownerships. Farmers in the study area are doing diversification by having off-farm activities and doing intensification by patterning crop to adapt rapid urbanization. To sustain the development of vegetable farming in peri-urban area, it will be crucial for government to create the new strategy of using vacant lands as farmlands to produce vegetables in order to combat food security issues, and also to assist farmers by upgrading their skill through various trainings.Keywords: Peri-urban, Strategy, Vegetable Farming.